Accelerate Synthesis in Ecology and Environmental Sciences - Carpenter, Stephen R.; Armbrust, E. Virginia; Arzberger, Peter W.; Stuart Chapin, F.; Elser, James J.; Hackett, Edward J.; Ives, Anthony R.; Kareiva, Peter M.; Leibold, Mathew A.; Lundberg, Per; Mangel, Marc; Merchant, Nirav; et al. (Bioscience, 2009)
Ecology is a leading discipline in the synthesis of diverse knowledge. Ecologists have had considerable experience in bringing together diverse, multinational data sets, disciplines, and cultural perspectives to address a wide range of issues in basic and applied science. Now is the time to build on this foundation and invest in ecological synthesis through new national or international programs. While synthesis takes place through many mechanisms, including individual efforts, working groups, and research networks, centers are extraordinarily effective institutional settings for advancing synthesis projects.